Deciphering the Anti-obesity Benefits of Resveratrol: The “Gut Microbiota-Adipose Tissue” Axis - Zhou, Liyuan; Xiao, Xinhua; Zhang, Qian; Zheng, Jia; Deng, Mingqun (Frontiers in Endocrinology, 2019)
Excessive white adipose tissue (WAT) accumulation due to an imbalance between caloric intake and energy expenditure (EE) characterizes the obesity. However, brown adipose tissue (BAT) is highly specialized for the dissipation of energy. Recent evidence indicated that the activation of BAT and the induction of WAT browning might be promising approaches to combat obesity by increasing EE and regulating glucose and lipid metabolism. Resveratrol, which is a polyphenolic compound, has been widely acknowledged to have protective effects against obesity and related metabolic disorders. The induction of WAT browning has been considered as one of the crucial factor in the metabolic benefits of resveratrol. Nevertheless, the specific mechanism that is involved is largely unclear. As a prebiotic-like polyphenol, resveratrol is able to modulate the composition of gut microbiota. In addition, in recent years, the impact of gut microbiota on the browning of WAT has received increasing attention and has been initially confirmed to play a role. By considering all these factors, this review explores the potential link between dietary resveratrol and the browning of WAT, which may be modulated by gut microbiota and their metabolites, and proposes the ‘gut microbiota- adipose tissue’ axis plays a vital role in the anti-obesity effects of resveratrol. This observation might provide novel insights and targets that could be used for fighting against obesity and associated metabolic disorders.